Bocca's hemipharyngo‐total laryngectomy for hypopharyngeal carcinoma to avoid reconstruction with a pedicled flap. Issue 7 (23rd March 2018) - Lucioni, Marco; Lionello, Marco; Salis, Gianni; Bertolin, Andy; Rizzotto, Giuseppe
Abstract: Background: Major pharyngeal defects after total pharyngolaryngectomy for hypopharyngeal squamous cell carcinoma (SCC) frequently demand reconstruction strategies that include myocutaneous pedicled flaps, such as the pectoralis major flap. Methods: We retrospectively reviewed the clinical charts of 24 patients with hypopharyngeal SCC treated with Bocca's hemipharyngo‐total laryngectomy (HPTL) at our Institution. Results: Eighteen patients (80%) experienced no disease recurrence after primary surgery and were alive with no evidence of disease after a mean follow‐up of 43 months. The 2‐year overall survival (OS) and disease‐specific survival (DSS) rates in our sample were 69% and 82%, respectively. Conclusion: Bocca's HPTL enables an immediate neopharyngeal reconstruction, and is indicated in selected patients with intermediate to advanced hypopharyngeal tumors.